A typical problem gambler affects six others. Issue 2 (4th May 2017) - Goodwin, Belinda C.; Browne, Matthew; Rockloff, Matthew; Rose, Judy
Abstract: While the financial and psychological burden on problem gamblers can be severe, at least some of the ill effects are also passed on to family or other close social ties. The present study estimated the number of affected-others for the typical problem gambler. Australian members of an online panel with gambling problems (N = 3076) and panel members who indicated that they had been affected by someone else's gambling (N = 2129) were asked to estimate the number of other people who were negatively affected by their gambling. Using robust statistics to analyse this data, the study found lower estimates made by problem gamblers (four affected people) compared to estimates made by affected others (six affected people, including the respondent). It was concluded that a point-estimate of six people affected is a more accurate figure since it does not suffer from self-presentation effects of problem gamblers. Low-risk and moderate-risk gamblers, unsurprisingly, affected far fewer other people (one and three, respectively). Both gamblers and affected-others most often identified close family members, including spouses and children, as the people impacted by others' gambling problems. These results provide an approximate measure of the number of people affected, per problem gambler, to facilitate accurate accounting of the harms accruing from gambling problems.